2018
DOI: 10.1016/j.tsf.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanocrystalline δ-MoN by thermal annealing of amorphous thin films grown on (100) Si by reactive sputtering at room temperature

Abstract: We report on the synthesis and characterization of nanocrystalline δ-MoN by crystallization of amorphous thin films grown on (100) Si by reactive sputtering at room temperature.Films with chemical composition MoN were grown using a deposition pressure of 5mTorr with a reactive mixture of Ar/(Ar+N 2 )=0.5. The as-grown films display mostly amorphous structure. Nanocrystalline δ-MoN phase is obtained after annealing at temperatures above 600 °C. The superconducting critical temperature T c depends on film thickn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…However, due to the thinness of the film, no preferential orientations for the Mo-N phases were observed in the X-ray diffraction spectrum, as previously confirmed [19]. Additionally, subjected to molybdenum oxides, for which the maximum intensities are around 20 to 30°, the signal is also weak.…”
Section: Xrd (X-ray Diffraction) Analysis Sem (Scanning Electron Micr...supporting
confidence: 77%
See 1 more Smart Citation
“…However, due to the thinness of the film, no preferential orientations for the Mo-N phases were observed in the X-ray diffraction spectrum, as previously confirmed [19]. Additionally, subjected to molybdenum oxides, for which the maximum intensities are around 20 to 30°, the signal is also weak.…”
Section: Xrd (X-ray Diffraction) Analysis Sem (Scanning Electron Micr...supporting
confidence: 77%
“…For example, N. Haberkorn et al made nanocrystalline MoN by crystallizing it with reactive DC sputtering at room temperature using a N2/(Ar+N2) = 0.5 mixture. They found that the annealed MoN film had an amorphous structure and a good superconducting critical temperature at about 170 nm thickness [19].…”
Section: Introductionmentioning
confidence: 99%
“…The small shift at the Mo + component ( 0.2-0.3 eV) observed for the pristine and irradiated films can be related to final state effects due to the presence of oxides that prevents the fast neutralization of the hole created during the photoemission process. No features related to the -MoN component are observed in the annealed film [21].…”
Section: Resultsmentioning
confidence: 93%
“…One feasible common solution was to obtain polycrystalline thin films by high‐temperature annealing after film deposition, which required both high‐temperature resistant equipment and unattainable optimized parameters. [ 24,25 ] The chemical synthesis method offers an alternative “bottom–up” approach that can synthesize high‐quality products, including single‐crystal thin films [ 26–28 ] and single‐crystal nanowires. [ 29–31 ] For example, Watson et al.…”
Section: Improvements In Fabrication Methodsmentioning
confidence: 99%
“…One feasible common solution was to obtain polycrystalline thin films by hightemperature annealing after film deposition, which required both hightemperature resistant equipment and unattainable optimized parameters. [24,25] The chemical synthesis method offers an alternative "bottom-up" approach that can synthesize highquality products, including single crystal thin films [26][27][28] and singlecrystal nanowires. [29][30][31] For example, Watson et al reported a method for fabrication of functional quantum dots by nanoskiving GaAs/AlGaAs quantumdotinnanowire systems that were grown using the autocatalytic vaporliquidsolid (VLS) approach (Figure 4b).…”
Section: Adaptation For Semiconductor Materialsmentioning
confidence: 99%